2009
DOI: 10.1166/jctn.2009.1232
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Study of Aminophenol Stability

Abstract: Quantum chemistry calculations at the B3LYP theory level, together with the 6-31G * basis set were employed to obtain energy (E), ionization potential (IP), bond dissociation energies (BDE), and spindensity distribution for aminophenol derivatives. Calculations of spin densities were performed for radical formed by hydrogen abstraction from the phenolic hydroxyl group. The IP and BDE values are related with more reactive and minus stable compounds. These values and also highest spin densities distribution on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…5 These metabolism and reactivity can be compared with salicylates metabolism 26 and p-aminophenol oxidation. 27 …”
Section: Resultsmentioning
confidence: 99%
“…5 These metabolism and reactivity can be compared with salicylates metabolism 26 and p-aminophenol oxidation. 27 …”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations indicated that for MTZ an initial hydrogen abstraction is approximately 94.07 (5), 100.60 (8), and 101.88 kcal/mol (7) at the C 7 , C 9 , and C 8 positions, respectively. The OH bond dissociation energy shows a high value of 108.22 kcal/mol (9).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the stability of the compounds can be observed by spin densities distribution. [23][24][25][26][27][28][29][30] The calculated spin density to initial electron abstraction (see Fig. 5) shows more contribution from the oxygen of carbonyl moiety for the 4 derivative (0.29), followed of 1 and 2 derivatives (0.27 and 0.26), and 3 derivative (0.16).…”
Section: Resultsmentioning
confidence: 99%